Comparison of available open-source shopping cart software - Huang, Shipeng (Jihočeská univerzita, 2023)
his thesis aims to compare seven open-source shopping cart software options, including Abante Cart, CE Phonix, Open Cart, Presta Shop, OS Commerce, Pimcore, and Zen Cart. The research will evaluate the user-friendliness, security, scalability, customization, ease of use, reliability, and performance of each software. The goal is to provide a comprehensive assessment for users to make informed decisions when selecting the best shopping cart software for their needs. Additionally, the thesis will provide developers and researchers with the latest information and trends on shopping cart software. The research findings will aid e-commerce companies in selecting the most suitable shopping cart software and enhancing their business efficiency and user experience.
Comparison of available open-source shopping cart software
Keywords: e-commerce; shopping cart software; open-source; user-friendliness; security; scalability; customization; ease of use; reliability; performance.; A ranking table and seven software icons: Abante Cart; CE Phonix; Open Cart; Presta Shop; OS Commerce; Pimcore; and Zen Cart.